The gothic novel in Ireland c. 1760-1829 - Morin, Christina (Manchester University Press, 2018)
The Gothic Novel in Ireland, 1760-1830 reveals how the Irish contribution to the rise of the gothic novel is all too frequently overlooked. Irish writers were actively engaged in shaping the form now conventionally understood as beginning with Horace Walpole's The Castle of Otranto (1764). Obviously an important text in the evolution of the gothic mode, the ostensibly pioneering Castle of Otranto was actually preceded by two Irish novels: Thomas Leland's Longsword (1762) and The Adventures of Miss Sophia Berkley (1760), by 'A Young Lady'. Neither of these texts overshadows Walpole's, but their omission from the literary history of the British gothic novel is nevertheless a telling indication of the exclusionary nature of current scholarly perspectives. Christina Morin's adroit and percipient text reveals how the Gothic was very much an international genre.